(untitled) (Marketing Journal, 2025)
This article substantiates the need to improve the economic development mechanisms of Uzbekistanʼs transport and logistics system . The analysis shows that modernizing logistics infrastructure , optimizing costs , and introducing advanced technologies can significantly enhance the competitiveness of the national transport and logistics network . Using the example of “Uzbekistan Railways ” JSC, the sectorʼs direct impact on the gross domestic product is modeled , and forecast indicators are developed up to 2027. The study applies SWOT analysis , regression techniques , and economic - mathematical modeling to formulate scientific recommendations for improving logistics efficiency . The results demonstrate the need to revise the national transport and logistics strategy and elevate it to a top priority of the national economic policy .